Records management practices for the collection of audio broadcast recordings of AM radio stations in Metro Manila an exploratory study - Enage, Amber Elaine V.; Lagrama, Eimee Rhea C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Records management practices entirely depend upon the nature of the holdings and the institution, and the competency of the records managers in these institutions. Just like any other institution, radio stations accumulate records daily and are subjected to record management practices. With this, the researcher surveyed the records management practices of two selected AM radio stations: DZAS Agapay ng Sambayanan 720 and Super Radyo DZBB 594. This determined and compared records management procedures of these AM radio broadcasting stations with regard to their collection of recorded broadcasts. An initial study was also performed with DZUP 1602 as the subject institution.
The respondents of the study were staff and personnel that were connected to DZAS Agapay ng Sambayanan 720 and Super Radyo DZBB 594. The researcher interviewed a Production Assistant and 2 Production Technicians from DZAS and also DZBB and DWLS's (GMA Network, Inc.'s flagship AM and FM radio stations) Radio Master/Radio Technician. The collection, from its creation until its storage and disposal, the tools and equipment used for the stations' records management procedures, the facilities, knowledge of the staff with regards to records management, the stations' financial resources, and the stations' efforts into preserving their collection were explored to meet the objectives of the study.
The following conclusions were drawn from the study: (1) Keeping audio recordings of their broadcasts is standard operating procedure for majority of radio stations; (2) Digital audio production has become common practice among radio stations, producing digital audio in .mp3 formats; (3) Due to the non-existence of standards for records management of recorded audio broadcasts and considering the limited knowledge of the radio stations' staff regarding records management, these institutions developed their own procedures to ensure the accessibility and usability of their collection; (4) As for budget allocation, the radio stations prioritize broadcasting equipment and maintenance. Not much is allocated for the maintenance of the audio recordings; (5) Being aware of their collection's importance in the growth of the country's heritage, these stations rarely dispose of their audio recordings; and, (6) These radio stations are not fully aware of the myriad procedures that come with the maintenance and preservation of digital audio. Despite this, their practices are sufficient to ensure the longevity of their collection.
With these conclusions, the researcher provides recommendations to help these institutions in the management of their audio recordings collection. This includes the development of a file naming scheme and proper metadata for their digital recordings, maintaining back-ups for their recordings, basic records management training for their staff, and the development of a digital audio preservation plan.
Given the importance of radio broadcasts as an integral aspect in the shaping of a country's national identity, management and preservation of these recordings are crucial. How these audio recordings are managed and preserved within the institutions that create them is a reflection of how the Philippine society and its people value the past and the present depicted by these broadcasts.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Records management; Radio stations -- Metro Manila